Species of Eupelmidae (Hymenoptera: Chalcidoidea) from the Fujian Tianbaoyan National Nature Reserve, China - Li, Zixuan; Xu, Shirui; Wang, Zongying; Chen, Pengfei; Wu, Jianqin; Peng, Lingfei (Zootaxa, 2025)
The Fujian Tianbaoyan National Nature Reserve, located in Fujian Province, southeastern China, has revealed a remarkable diversity of Eupelmidae (Hymenoptera) species through several years of investigation. Fourteen species are newly recorded from this reserve, including two new species, Australoodera chenghuang Li & Peng sp. nov. and Zaischnopsis tianbaoyanensis Li & Peng sp. nov. One genus, Australoodera Girault n. rec. and one species, Eupelmus iris Fusu & Gibson n. rec. are newly recorded for China, the other eleven species include Anastatus gansuensis Chen & Zang, A. gastropachae Ashmead, A. japonicus Ashmead, A. shichengensis Sheng & Wang, Coryptilus longicervix Kawano & Fusu, Eupelmus luteipes Fusu & Gibson, E. peculiaris Narendran, E. pini Taylor, E. testaceiventris Motschulsky, Zaischnopsis fumosa Peng & Xiang, and Z. pacis Jiang & Peng. All species are illustrated, with the two new species described and illustrated in detail. Additionally, COI sequences for the two new species and five other eupelmids from the reserve are provided.